Parabiosis Reveals Leukocyte Dynamics in the Kidney - Lever, Jeremie M. (Lab Invest, 2017)
The immune cellular compartment of the kidney is involved in organ development and homeostasis as well as in many pathological conditions. Little is known about the mechanisms that drive intrarenal immune responses in the presence of renal tubular and interstitial cell death. However, it is known that tissue resident leukocytes have the potential to play distinct roles compared with circulating cells. We used a parabiosis model in C57BL/6 CD45 congenic and GFP transgenic mice to better understand the dynamics of immune cells in the kidney. We found F4/80(Hi) intrarenal macrophages exhibit minimal exchange with the peripheral circulation in two models of parabiosis, whether mice were attached for 4 or 16 weeks. Other intrarenal inflammatory cells demonstrate near total exchange with the circulating immune cell pool in healthy kidneys, indicating that innate and adaptive immune cells extensively traffic through the kidney interstitium during normal physiology. Neutrophils, dendritic cells, F4/80(Low) macrophages, T cells, B cells, and NK cells are renewed from the circulating immune cell pool. However, a fraction of double negative T (CD4(−) CD8(−)) and NKT cells are long-lived or tissue resident. This study provides direct evidence of leukocyte subpopulations that are resident in the renal tissue, with minimal to no exchange with the peripheral blood. In addition, the data demonstrate continual exchange of other subpopulations through uninflamed tissue.